Effect of Income Shocks on Households’ Health and Consumption: A Case Study of Civil Servant Farming Households in South West, Nigeria - Abdulaleem, M. A; Fakayode, S. B; Adio, M. O (Advances in Social Sciences Research Journal, 2023)
Income shocks have continued to aggravate conflicts in several parts of Nigeria and many other countries of the world. The frequent occurrence of income shocks among the populace coupled with a lack of effective coping mechanisms has increased the households’ vulnerability to poverty, poor health, and lower food consumption. This study examined the effects of income shocks on health and consumption as well as the coping mechanisms adopted by the farming civil servant households in Southwest, Nigeria. A multistage sampling technique was used to select 360 farming Civil Servants used in the study. A combination of Descriptive Statistics and the Likert Scale was used for the data analysis. The result revealed that deteriorating health conditions ( = 3.79) and reduced food consumption ( = 3.28) were the major consequences of income shocks in the study area. The study further revealed that sales of assets or property ( =2.59) and sourcing financial support from affiliated religious bodies ( =2.59) remains the most common coping strategies adopted by Civil Servants to mitigate income shocks in the study area. Therefore, the study recommended the institutionalization of a Health Insurance Scheme for Civil Servants to provide adequate and easy access to health care. Also, to avoid assets and property loss, improving the standard of living of civil servants through prioritized salary payment, access to the loan market, and empowerment using incentives become imperative.